Wear promoted in the apical third of simulated canals after instrumentation with protaper universal system (Journal of Applied Oral Science, 2009)
OBJECTIVE: This study evaluated the wear in the apical third of simulate canals after preparation with ProTaper Universal Rotary System. MATERIAL AND METHODS: 24 sets of instruments were used in 24 simulated canals in transparent epoxy resin blocks with degree of curvature of either 20°or 40°. The canals were photographed preoperatively and after preparation of the apical stop with ProTaper F3, F4 and F5 instruments. The initial and final images were exported to Adobe Photoshop® software and superimposed to detect the root canal wall differences (in mm) between them, in two points located 1 (A) and 5 (B) mm from the point where the working length was established. Data were subjected to analysis of variance to verify the existence of interaction among the factors: canal curvature, instrument size and curve location. Significant level was set at 5%. RESULTS: Regardless of the location and the canal curvature, F4 and F5 instruments produced the greatest wear (p